2(2x+2)=-5(2x-1)+3x

Simple and best practice solution for 2(2x+2)=-5(2x-1)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+2)=-5(2x-1)+3x equation:


Simplifying
2(2x + 2) = -5(2x + -1) + 3x

Reorder the terms:
2(2 + 2x) = -5(2x + -1) + 3x
(2 * 2 + 2x * 2) = -5(2x + -1) + 3x
(4 + 4x) = -5(2x + -1) + 3x

Reorder the terms:
4 + 4x = -5(-1 + 2x) + 3x
4 + 4x = (-1 * -5 + 2x * -5) + 3x
4 + 4x = (5 + -10x) + 3x

Combine like terms: -10x + 3x = -7x
4 + 4x = 5 + -7x

Solving
4 + 4x = 5 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
4 + 4x + 7x = 5 + -7x + 7x

Combine like terms: 4x + 7x = 11x
4 + 11x = 5 + -7x + 7x

Combine like terms: -7x + 7x = 0
4 + 11x = 5 + 0
4 + 11x = 5

Add '-4' to each side of the equation.
4 + -4 + 11x = 5 + -4

Combine like terms: 4 + -4 = 0
0 + 11x = 5 + -4
11x = 5 + -4

Combine like terms: 5 + -4 = 1
11x = 1

Divide each side by '11'.
x = 0.09090909091

Simplifying
x = 0.09090909091

See similar equations:

| 36j^2-5j=0 | | 2x+16=58 | | 18r+3=72-5r | | 8x+7x-4x-5=61 | | 8x+7x-4x-5= | | y=1.5x+14 | | 14524=3.14x^2(5.5) | | 45-m=25 | | y=14x+1.5 | | y-3=6/5(x-3) | | x+20=78 | | 3j^2+19j+16=0 | | 43k^2+27k=0 | | VXYZ/UVXYZ | | -3-17m=54 | | 3-2x-7+3=x-4 | | 5x+6x-2x-5=58 | | -8x-45=15-28x | | 12/1.27 | | -3-2n=-17 | | 10x-4=90 | | 2k+3=6k-4 | | 32+14y=4 | | 8-2(p-6)=52 | | 5/11=p/17 | | 52x^3+13x^4= | | 5u^2+18u+9=0 | | -4+8n=-78 | | 100*0.14*2= | | 4s-10=s+11 | | 3(12-x)=4+5X | | (-2)-9=-11 |

Equations solver categories